2008
DOI: 10.1136/ip.2006.013508
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of drowning deaths in a surf beach swimmer and surfer population

Abstract: adult males, international tourists, people with cardiovascular conditions, and exposure to rip currents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 12 publications
4
48
0
Order By: Relevance
“…This estimation of proportional crude water exposure corresponds approximately with drowning death data, where 16% of recreational surf bather fatalities were associated with surf craft, suggesting that floatation devices (e.g., surfboards) do not offer drowning protection (Morgan et al, 2008). Further investigation is required because surfers on average may be exposed to higher drowning risk conditions (e.g., larger waves, greater distance from shore) and over longer durations compared with swimmers or waders though this may be compensated by greater aquatic skills and experience in surf.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…This estimation of proportional crude water exposure corresponds approximately with drowning death data, where 16% of recreational surf bather fatalities were associated with surf craft, suggesting that floatation devices (e.g., surfboards) do not offer drowning protection (Morgan et al, 2008). Further investigation is required because surfers on average may be exposed to higher drowning risk conditions (e.g., larger waves, greater distance from shore) and over longer durations compared with swimmers or waders though this may be compensated by greater aquatic skills and experience in surf.…”
Section: Discussionsupporting
confidence: 60%
“…Comparable results were found for the time-period 2 data collection. Morgan et al (2008) reported just one out of 129 surf bather drowning deaths over a four-year period in Australia was recorded to have occurred between the flags. Fenner, Harrison, Williamson, and Williamson's (1995) statistical study of surf lifesaver resuscitations-for the Australian state of Queensland from 1972 to 1993-demonstrated that the likelihood of successful resuscitation increased closer to the lifesaver supervised zone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idealised schematic in (c) shows that water transported onshore by breaking waves is either recirculated by rip currents within the surf zone or carried seaward through a narrow rip neck where it dissipates in an expanding rip head. investigated the general behaviour and safety awareness of beachgoers (see for example: Ballantyne et al, 2005;Moran, 2006Moran, , 2008Wilks et al, 2007;McCool et al, 2008McCool et al, , 2009Morgan et al, 2008;Sherker et al, 2010). Recently, several studies have attempted to link the physical behaviour of rip currents with the incidence of drowning and swimmer response to being caught in rip currents (MacMahan et al, 2010;Houser et al, 2011;Miloshis and Stephenson, 2011).…”
Section: Introduction and Aimsmentioning
confidence: 99%